2022
DOI: 10.1097/gox.0000000000004469
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting in the Upper Extremity: Defining New Indications

Abstract: Background: Autologous fat grafting is a commonly used technique in plastic surgery that can also be applied broadly in hand surgery. We present a case series to demonstrate the diverse indications for fat grafting in hand surgery. Methods: We retrospectively reviewed cases of fat grafting in the upper extremity in 2020. Cases representing a unique application of fat grafting were identified. Patient data, including demographics, diagnoses, preoperative and postoperative assessments, complications, patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, some clinical studies have shown that fat grafting used in tendon repairs reduced adhesions and it has been recommended as a method with a positive effect on outcomes especially in flexor tendon repairs. 19,20 Thus, local adipose tissue grafting has been shown to be an easy-to-apply, low-cost method that provides successful results. 13 In the current study, for the first time in literature, the application of fat graft, which is a low-cost, easy-to-apply, and easily accessible method, was used in experimental tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some clinical studies have shown that fat grafting used in tendon repairs reduced adhesions and it has been recommended as a method with a positive effect on outcomes especially in flexor tendon repairs. 19,20 Thus, local adipose tissue grafting has been shown to be an easy-to-apply, low-cost method that provides successful results. 13 In the current study, for the first time in literature, the application of fat graft, which is a low-cost, easy-to-apply, and easily accessible method, was used in experimental tendon healing.…”
Section: Discussionmentioning
confidence: 99%